INVENTARISASI JENIS-JENIS TUMBUHAN BERKHASIAT OBAT DI DESA TANJUNG BARU PETAI KECAMATAN TANJUNG BATU KABUPATEN OGAN ILIR (OI) PROVINSI SUMATERA SELATAN - Kartika, Trimin (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2015)
Research on Inventory the types of medicinal plants has been carried out in February-March 2015 in the village of Tanjung Baru district of Tanjung Batu Petai Ogan Ilir South Sumatra Province . The study aims to determine the types of medicinal plants are used and bian and the efficacy of the plant . Research using the direct orientation . The results showed that the types of medicinal plants divisio consists of 1 , 2 classes , 31 orders , 33 familia , 40 genera and 40 species. Parts of medicinal plants that are used as raw materials which have medicinal properties in the form of leaves, roots / rhizomes , stems , bark , fruit , flowers, seeds and sap . Efficacy of medicinal plants for people to use as raw material in traditional medicine .Â Key words : Medicinal plants, inventarisation